2016
DOI: 10.4137/ebo.s39675
|View full text |Cite
|
Sign up to set email alerts
|

Article Commentary: Virus Discovery Using Tick Cell Lines

Abstract: While ticks have been known to harbor and transmit pathogenic arboviruses for over 80 years, the application of high-throughput sequencing technologies has revealed that ticks also appear to harbor a diverse range of endogenous tick-only viruses belonging to many different families. Almost nothing is known about these viruses; indeed, it is unclear in most cases whether the identified viral sequences are derived from actual replication-competent viruses or from endogenous virus elements incorporated into the t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
19
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
3

Relationship

4
3

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 53 publications
3
19
0
Order By: Relevance
“…For the first time we showed that the ALSV strain Miass527 can persist in tick cells for at least three years. It was previously shown that the tick cell line IRE/CTVM19 may harbour an unknown rhabdovirus (31). Our experiment confirmed the presence of a rhabdovirus and suggests that it does not interfere with the persistence and active reproduction of Alongshan virus in IRE/CTVM19 cells.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…For the first time we showed that the ALSV strain Miass527 can persist in tick cells for at least three years. It was previously shown that the tick cell line IRE/CTVM19 may harbour an unknown rhabdovirus (31). Our experiment confirmed the presence of a rhabdovirus and suggests that it does not interfere with the persistence and active reproduction of Alongshan virus in IRE/CTVM19 cells.…”
Section: Discussionsupporting
confidence: 84%
“…We used cell culture supernate collected after one passage of strain Miass527 in IRE/CTVM19 cells, at 17, 19, 20 and 32 months after initial isolation for transmission electron microscopic examination. The IRE/CTVM19 tick cell line was recently reported to contain RNA sequences with similarity to rhabdoviruses (31). To prevent confusion between ALSV and this putative rhabdovirus in our microscopic examination, we first screened the pellet obtained after ultracentrifugation of uninfected IRE/CTVM19 for rhabdovirus RNA using specific primers (Supplementary file 2).…”
Section: Transmission Electron Microscopymentioning
confidence: 99%
“…A number of options for functional characterization of these viruses are available but they unfortunately require work. Additional culture models are needed to handle all the new discoveries and genetic engineering methods for more easily establishing cell lines from exotic species are worth pursuing (Ettayebi et al, 2016;Finkbeiner et al, 2012;Stenglein et al, 2012;Bell-Sakyi and Attoui, 2016;Janowski et al, 2017). Focusing discovery on genetically tractable organisms has allowed for relatively rapid functional studies of the new discovered C. elegans Orsay virus Jiang et al, 2017).…”
Section: Experimenting With Functionmentioning
confidence: 99%
“…Generally, very little is known about tick genome organisation, or how and how often viral elements become integrated into a tick genome (26) and for what reasons. We identified ORFs related to mobile genetic elements as well as repeat regions and possible target site duplications formed by the integration of mobile genetic elements adjacent to the ASFLI-elements.…”
Section: Discussionmentioning
confidence: 99%